Rejection of Marriage in Medieval Dubrovnik - Nikolić, Zrinka (Array, 1999)
On the bases of legislature and individual case studies, the author presents the circumstances in which came to rejection of marriage in medieval Dubrovnik, and the attitude of the government of Dubrovnik towards it.